# Math

posted by .

Solve the following equation.

4.7 = 1.13x^2

Do i square root the 1.13x^2 first? or divide both sides by 1.13?

• Math -

Please excuse my dear aunt sally

• Math -

Both will work, but it is customary to divide both sides by 1.13, which avoids an extra square-root:

4.7=1.13x²
x²=4.7/1.13
x=√(4.7/1.13)

or

√(4.7)=√(1.13)√(x²)
x=√(4.7)/√(1.13)

• Math -

haha sorry. i didn't bother to read the entire thing. you must divide first in order to root both sides

## Similar Questions

1. ### math

Still looking at how to solve these... Both are cubic polynomials?
2. ### Algebra

Can you pleas Solve the quadric equation step by step 4x square =13x+2 4x^2 = 13x + 2 subtract 13x and 2 from both sides 4x^2 - 13x - 2 = 0 Now use the quadratic formula, since it does not factor.
3. ### math,algebra

is this correct? solve: 9x^2=14 this is what i did: i divide 9 by both sides x^2=1.6 is this first step right Then take the square root of both sides. x^2=1.6 you said to take the squar root of both sides. so is this correct x = 1.264911
4. ### Algebra

Can someone verify if my answers are correct?
5. ### math/algebra

subtract. express in simplest form 13x/30 - 4x/ 15 = factor the first denominator. Get a common denominator. Combine terms. I will be happy to critique your work. ok 13x/30 - 4x/ 15 = This is where I get lost, I know that I have to …
6. ### Algebra

Solve 2+ the square root of 4-x=x what is your question?
7. ### Pre Algebra

Please help me with some problems. Thank you! Solve the equation by square root property. 3. 2x^2 = 26 I don't understand how to solve this problem. Solve the equation using the quadratic formula. 7. 7x^2=-8x -2 This is what I got …
8. ### Algebra

I have a few questions that I need help with. Solve the radical equation, and check all proposed solutions. 5. x- square root 3x-2=4 I don't understand this problem. Solve and check the equation. 10. (x^2+14x+49)^3/4-20=7 would I have …
9. ### Algebra

Hello all - I would like to check my work on 2 problems. Solve by factoring : x^2-13x= -12 x^2-13x+12= -12 + 12 x^2-13x+12= 0 (x-1)(x-12)= 0 x = 1 , 12 Solve using the square root property: 2x^2-35=15 2x^2-35-15=0 2x^2-50=0 2(x-5)(x+5)=0 …
10. ### intermidate algebra

Solve each equadratic equation by factoring. 6^2-13x-28 36-13x-28 -13x=-36+28 x=64/13 check this, correct if wrong

More Similar Questions